Thyroid surgery performed on an overnight basis: a 17 years of experience - Alberto Salgueiro Molinari; Alberto Treiguer; Vinicius Grando Gava; Jose Luiz Brum Rojas; Paulo Ernani Evangelista; Iracema Gonçalves; Airton Golbert (Archives of Endocrinology and Metabolism, 2015)
Objective This study aimed to evaluate the results of thyroid surgeries with hospitalization periods shorter than 18 hours performed in a surgical endocrinology service, correlating these results with type of procedure, the definitive diagnosis and complications associated with the procedure.Subjects and methods The procedures performed, complications associated, hospitalization period, and relationships among these variables were assessed in consecutive patients subjected to different types of thyroid surgeries from January 1997 to March 2014 by the same group of surgeons. Data were analyzed by frequency, and the associations between the hospitalization period and other variables were analyzed using the Pearson chi-square test and Fisher’s exact test, using a multiple comparisons test with Bonferroni correction.Results Among the 3,411 surgeries performed, 799 of them were malignant neoplasia, 2,505 were benign tumors and 107 were Graves’ disease. The following procedures were performed: total thyroidectomy (1597 patients); total thyroidectomy with neck exploration (369 patients); lobectomy plus isthmectomy (1084 patients); total thyroidectomy complementation (145 patients); total thyroidectomy with neck dissection (84 patients); modified radical total thyroidectomy (13 patients); nodulectomy (11 patients); unresectable (9 patients); central neck dissection (48 patients); lateral neck dissection (38 patients); and others (13 patients). The following surgical complications, characteristic of the procedure: hemorrhage in 41 (1.2%) patients, hypoparathyroidism in 10 (0.3%) patients and recurrent laryngeal nerve (RLN) injury in 23 (0.7%) patients. Hospitalization shorter than 18 hours was observed in 97% of patients.Conclusion Thyroid surgery can be safely performed in virtually all patients on an overnight basis in specialized services.